Parental Pain Catastrophizing, Communication Ability, and Post-surgical Pain Outcomes Following Intrathecal Baclofen Implant Surgery for Patients With Cerebral Palsy - Byiers, Breanne J.; Roberts, Caroline L.; Burkitt, Chantel C.; Merbler, Alyssa M.; Craig, Kenneth D.; Symons, Frank J. (Frontiers in Pain Research, 2022)
There is strong evidence that psychosocial variables, including pain catastrophizing, influence parental and child ratings of pain, pain expression, and long-term outcomes among children with chronic pain. The role of these factors among children who have communication deficits due to cerebral palsy (CP) and other intellectual and developmental disabilities is currently unclear. In this study, parental pain catastrophizing was assessed before intrathecal baclofen (ITB) pump implantation for spasticity management in 37 children and adolescents with CP, aged 4 to 24 years. Pain was assessed before and after surgery with two methods: a parent-reported pain interference scale, and behavioral pain signs during a standardized range of motion exam. Linear mixed models with clinical/demographic factors and scores from the pain catastrophizing scale for parents (PCS-P), and scores on the communication subscale of the CPChild as predictors and the pain variables as the outcomes were implemented. On average, both pain outcomes improved after surgery. The interaction between parental pain catastrophizing and communication scores predicted the slope of behavioral reactivity scores over time, with dyads with the high PCS-P scores and high communication scores showing the least improvement. High PCS-P scores and low communication scores were associated with higher pain interference ratings overall, but none of the variables showed significantly predicted change in pain interference. Future work is needed to investigate the parental behaviors that mediate the relationships between parental catastrophizing and pain outcomes in this population.